Determination of CO2 Content in Aqueous Samples by Closed Simple Distillation System: Application to Beverages Available in Saudi Market - Amir, Hussain (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
The determination of carbon dioxide (CO2) in aqueous solutions is important for process and quality control in industries such as the beverage industry. The currently popular CO2 process analyzer relies on Henry's law, which states that the volume of a gas dissolved in a liquid is proportional to its partial pressure at a given temperature. However, this method is not selective for CO2 and can be influenced by other gases present in the liquid, leading to interferences. In this study, a novel method for the direct determination of CO2 in aqueous solutions was investigated using a closed simple distillation system. The samples tested were carbonated soft drinks available in the local Saudi market. The experimental set up for the simple distillation involved transferring 3ml of a sample into a round bottom flask and fitting it with condensers. The temperature of the heating mantle was then slowly increased, and the pressure gauge was used to detect the CO2 gas at temperatures of 50°C and 60°C. The monomeric pressure obtained was used to calculate the amount of CO2 in the sample. The closed system was checked for leaks to ensure accurate results. The results of the study showed that the determination of CO2 using the closed simple distillation system was successful. This method offers a direct and selective approach for determining CO2 content in aqueous solutions, particularly in situations where other gases are also present in the liquid. The novel method can be applied to the analysis of CO2 content in various beverages available in the market, including carbonated soft drinks.